2020
DOI: 10.1126/sciadv.abc8257
|View full text |Cite
|
Sign up to set email alerts
|

Mus81-Eme1–dependent aberrant processing of DNA replication intermediates in mitosis impairs genome integrity

Abstract: Chromosome instability (CIN) underpins cancer evolution and is associated with drug resistance and poor prognosis. Understanding the mechanistic basis of CIN is thus a priority. The structure-specific endonuclease Mus81-Eme1 is known to prevent CIN. Intriguingly, however, here we show that the aberrant processing of late replication intermediates by Mus81-Eme1 is a source of CIN. Upon depletion of checkpoint kinase 1 (Chk1), Mus81-Eme1 cleaves under-replicated DNA engaged in mitotic DNA synthesis, leading to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 67 publications
(162 reference statements)
1
25
0
Order By: Relevance
“…DDR-directed therapies have been introduced in clinical trials recently (Pilié et al, 2019 ). However, chromosomal instability (CIN) is the dominant drawback of this strategy, which conversely underpins evolution and growth of tumor cells (Bakhoum and Cantley, 2018 ; Calzetta et al, 2020 ). Thus, knowledge of the interactions among multiple DDR pathways and understanding the discrepant functions of DDR-relevant proteins in various cancers contribute to efficient cancer therapy and needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…DDR-directed therapies have been introduced in clinical trials recently (Pilié et al, 2019 ). However, chromosomal instability (CIN) is the dominant drawback of this strategy, which conversely underpins evolution and growth of tumor cells (Bakhoum and Cantley, 2018 ; Calzetta et al, 2020 ). Thus, knowledge of the interactions among multiple DDR pathways and understanding the discrepant functions of DDR-relevant proteins in various cancers contribute to efficient cancer therapy and needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Coordinated cleavage of replication forks could be proceeded by TRAIP/p97-dependent unloading of the CMG helicase (Deng et al, 2019), leaving stretches of vulnerable ssDNA at the leading strands. Although the responsible nuclease in processing under-replicated DNA upon PARP inhibition remains elusive, MUS81 has been shown to be active during mitosis (Calzetta et al, 2020; García-Luis and Machín, 2014; Wild et al, 2019; Wyatt et al, 2013), to localize to under-replicated DNA in mitosis (Di Marco et al, 2017), and to act on stalled replication forks in mitosis (Fugger et al, 2021; Zimmermann et al, 2013). However, our data showed that depletion of MUS81 alone was not sufficient to reduce SCEs, possibly due to redundancy with other endonucleases that are active during mitosis (Chan and West, 2014; Wyatt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, under certain conditions, the same endonucleases can promote CIN instead of preventing it. For example, in CHK1 depleted samples, MUS81 and its cofactor EME1 augment bulky chromosome bridges and MN frequency in a manner that is associated with nucleoside-shortage mediated aberrant processing of UR-DNA [ 72 , 73 ].…”
Section: The Crucial Role Of Nucleases In Cin Preventionmentioning
confidence: 99%
“…For example, CHK1 inhibitors induce cell death and accumulation of both bulky chromosome bridges and MN. A mitosis-specific pathway involving MUS81 endonuclease, its partner EME1, and MiDAS components RAD52 and POLD3 promote the accumulation of such CIN markers, with no effect on the extent of cell death [ 72 ]. While it is still unclear whether precluding acute CIN during cancer treatments suffices to prevent the acquisition of genome instability, it is tempting to speculate that the limitation of acute CIN could benefit the outcome of cancer treatments.…”
Section: Cin and Cancer Therapiesmentioning
confidence: 99%